A RETROSPECTIVE STUDY: COMPARISON OF OPTIC NERVE SHEATH DIAMETER TO EYEBALL TRANSVERSE DIAMETER RATIO (ONSD/ETD) WITH COMPUTER TOMOGRAPHY ROTTERDAM AND GLASGOW OUTCOME SCALE. - B V S Raman; Pradeep Tavva; Pydi Krishna Rajiv; Peri Lakshmi Divya (Student’s Journal of Health Research Africa, 2024)
Objectives This study aims to examine the correlation between optic nerve diameter, global transverse diameter, and correlation with CT Rotterdam score and GOS. Methods A retrospective study of head injury patients who underwent craniotomy was carried out to assess the optic nerve diameter, global transverse diameter, as well as the ratio of pre-and post-operative values. In addition to this, the study also noted the GOS and CT Rotterdam score of each patient, and the correlation between the measure parameters and the GOS and CT Rotterdam score using Pearson’s correlation coefficient. Results The study revealed a strong positive correlation between the ratio of pre-and post-operative values and the CT Rotterdam score, as well as a strong positive correlation between the optic nerve diameter, global transverse diameter, and the CT Rotterdam score. Additionally, a moderate negative correlation between the optic nerve diameter, globe transverse ratio, and the GOS score was also noted. Conclusion The comparison of ONSD/ETD ratios in pre and post-operative TBI patients showed a significant reduction in the ratio following surgical intervention, indicating a decrease in elevated ICP. The preoperative ONSD/ETD ratio demonstrated a positive correlation with Rotterdam CT scoring, suggesting its potential as a marker of intracranial pathology. However, its utility in predicting functional outcomes as measured by GOS was not significant. Recommendation The study recommends further research to validate the clinical utility of ONSD/ETD ratio measurements in assessing brain injury severity and predicting outcomes.